Post-COVID-19 strategies for higher education institutions in dealing with unknown and uncertainties - Rasli, Amran; Tee, Mcxin; Lai, Yin Ling; Tiu, Zian Cheak; Soon, Eu Hui (Frontiers in Education, 2022)
COVID-19 global pandemic outbreak has presented higher education institutions with impediment of transforming to new curriculum, pedagogy, and educational management. Inevitable transformation in higher education triggered by COVID-19 is still ongoing albeit most countries are now at endemic stage. However, transformation should not just about simply change instructional delivery. COVID-19 pandemic is unique opportunity for educators and policy makers to rethink about education systems, and to reimagine what is important, necessary, and desirable for future generations. Hence, this study focuses on identifying strategies for higher education institutions to deal with unknown and uncertainties during and post pandemic. Expert Opinion Method was conducted involving five professors who are senior management in their respective universities and have been directly involved in formulating strategies and policies during pandemic. Four major dimensions were developed from findings: 1. Resilience and Change Management, 2. Digital Transformation and Online Learning, 3. Curriculum Change, and 4. Sustainability. Flexibility is also the most common issue discussed by experts. Based on thematic analysis, post COVID-19 strategic framework for higher education institution sustainability is proposed. In addition, this study can be ideas of roadmap for educators, policy makers and all relevant stakeholders to prepare for future disruptions in the education sector.